Enhancing production and productivity of oilseed Brassica: research need for 21st century (Journal of Oilseed Brassica, 2026)
India is one of the largest cultivators of oilseeds crop Per capita consumption of vegetable oils has increased from 6.2 kg/year in 1986-87 to 14.2 kg/ year during 2012-13 this eventually pushes the demand for oil significantly.